Rethinking Fascism the Italian and German dictatorships - Di Michele, Andrea 1968-; Focardi, Filippo 1965- (Studies in early modern and contemporary European history, 2022)
Intro -- Contents -- Introduction -- I. Fascism and Nazism in a Transnational Key -- German Historiography on National Socialism in Its Transnational Context -- Roberta Pergher Italian Fascism in Transnational Historiography -- II. "Volksgemeinschaft" and the Relationship between Italian Society and Fascism -- From Debates on the Political Order to Visions of Community -- Beyond Consensus: Rethinking Italian Fascism -- III. The Dictators: Hitler and Mussolini -- Adolf Hitler and Benito Mussolini -- Benito Mussolini: 100 Years on -- Adolf Hitler -- IV. Violence -- "Spaces" of Violence -- Fascist Violence. History and Historiography -- V. Stone Fascism after the War -- Obersalzberg and the Axis -- Traces of Fascist Architecture in Republican Italy -- Fascist Monuments on the Border. The Case of Bolzano/Bozen, South Tyrol -- VI. The New Right and Fascism -- "Sempre Presente?" -- Old Ideologies and New Strategies. German Right-Wing Populism -- CasaPound Italia and Forza Nuova. Back to the Future -- Contributors.